Literacy for Peace: A Program to Prevent Bullying and Promote Positive Character in Elementary School - Winarto, Eline Rozaliya; Siti Nuraeni, Rani; Mayasari, Ria; Khairana, Rika; Hildayanti, Rima; Septiana, Risna; Meilin, Rizka Karima (JURNAL ABDIMAS SERAWAI, 2025)
Bullying in schools can harm children' mental and emotional well-being and possibly result in poor character traits down the road. Bullying has negative effects on learning environments, trauma, and self-confidence. It is crucial to put bullying prevention into practice in order to address this problem. In the community, at school, and at home, literacy activities help youngsters develop morality and comprehend information. This community service was provided using an organized way during the PPL 1 Program at SDN Silih Asuh 2. Enhancing the pupils' literacy culture is the goal of this community service project. Through the "True Friends Do Not Bully" exercise, SDN Silih Asuh 2's literacy program blends character education with literacy abilities. The community service includes preparation, cooperation with guiding lectures and supervising teachers, and the execution of socializing and contests. In addition to outreach initiatives involving students in grades 1–6, this activity includes poetry, short story writing contests, posters for higher classes, and coloring pages for younger grades. Students' creativity is stimulated and literacy is improved through this practice. Students' writing abilities, creative expression, and comprehension of anti-bullying principles are all enhanced as a consequence of this set of exercises. Additionally, there are tangible results in the shape of a book that compiles the students' best poetry and short tales. Because it encourages the integrated development of students' literacy and character, this activity can be used as a model by other educational institutions.